AN ANALYSIS CLASSROOM INTERACTION IN ENGLISH SUBJECT AT SENIOR HIGH SCHOOL - Dosma Mutiara Purba; Rafika Dewi Nasution; Lidiman S.M. Sinaga (Universitas Negeri Medan, 2017)
This study focuses on analyzing the process of classroom interaction through Flanders Interaction Analysis Category (FIAC) model. The objective was to decsribe how the teacher and students use the categories of classroom interaction in English class by using Flanders Interaction Analysis Category (FIAC) model. The data was found based on the data transcription . the source of the data was the utterances between English teacher and 10th grade students at SMA N 2 Doloksanggul. The instruments for the data collection was video recording. The data analysis applied descriptive qualitative research. It was found that the total percentage each categories classroom interaction were Accepts Feeling (1.1%), Praise and Encourages (2.4%), Accepts Ideas of Students (1.2%), Asks Questions (18.8%), Lecturing (25%), Giving Directions (17.8%), Critizising or justifying authority (2%), Student Talk Response (15.3%), Student Talk Initation (1.9%), Silence or Confusion (14.5%). The dominant category of Teacher Talk in English classroom interaction at SMA N 2 Doloksanggul was Lecturing (25%). While The dominat category of Students Talk was Students Talk Response (15.3%). Keywords : Teacher Talk, Student Talk, Flanders Interaction Analysis Categories (FIAC) model.